A influência das pressões institucionais na divulgação dos projetos de mudanças climáticas em empresas de petróleo e gás natural - Albuquerque, Sâmia Raquel Castor (2013)
The study aims to investigate isomorphic forces that legitimize practices related to climate change projects, evidenced in Social and Environmental Reports of oil companies, released by Fortune. The methodology developed in this research has an exploratory characteristic with qualitative approach and has the assistance of the software NVivo 10 for processing the data collected. The study was conducted on a sample of 35 companies and, through categories codification and cluster analysis, the organizations that have the most complete information on your socio-environmental report have the best placements in the ranking compiled by Fortune. The survey results still indicate that larger organizations are more likely to obtain predominant features of the normative pillar, since multinationals have significant visibility handle this broader spectrum and complex pressures of sustainable development in its operations. Hence, they adopt the models of the industry in which they are embedded in their local context, weakening consequently the predominance of the mimetic pillar. Thus, there were exceptions in companies in less developed countries because, although lead the first places in the Fortune, did not possess satisfactory performance with respect to quality of such disclosure. Therefore, it is argued that environmental issues are often neglected in less developed countries, where the focus on climate change may not be as important as the need for social investments to combat poverty, for example. As a result, also argues that multinationals do not suffer so many pressures of coercive isomorphism as the normative, because there is a lack of clear regulations and enforcement mechanisms at the international level. Finally, it was concluded that the oil companies have made use of three types of isomorphism in the period surveyed as a strategy for the dissemination of their Corporate Social Responsibility practices relating to climate change projects.